Enhanced Electrochemical Performance of Non-Aqueous Li-O2 Batteries with Triethylene Glycol Dimethyl Ether-Based Electrolyte. Issue 6 (27th April 2017) - Wu, Chaolumen; Li, Taoran; Liao, Chenbo; Xu, Qingkai; Cao, Yuancheng; Li, Lei; Yang, Jun
Abstract : Triethylene glycol dimethyl ether (G3) is evaluated as an electrolyte solvent for non-aqueous lithium-oxygen (Li-O2 ) batteries. A liquid electrolyte of 1 M LiTFSI in G3 shows lower viscosity, higher oxygen solubility and diffusion, higher ionic conductivity and lithium ionic transference number compared to the conventional liquid electrolyte of 1 M LiTFSI in tetraethylene glycol dimethyl ether (G4). Then the Li-O2 battery using the G3-based electrolyte shows better cycling stability and higher rate capability compared to the battery using the G4-based electrolyte. At a higher current density of 2.5 A gcarbon −1, the discharge capacity of the battery using the G3-based electrolyte is about 1472 mAh gcarbon −1, which is about four times higher than that of the battery using the G4-based electrolyte. At current density of 1 A gcarbon −1 with a fixed capacity of 1000 mAh gcarbon −1, the battery using the G3-based electrolyte can be operated stably for 80 cycles, while only 20 cycles are achieved by using the G4-based electrolyte. Therefore, we think the G3-based electrolyte could be a proper alternative electrolyte to the conventional G4-based electrolyte for the development of Li-O2 batteries.